Desenvolvimento de clones de batata de alta qualidade de tubérculo a partir de genitores resistentes a requeima - Costa, Liege Camargo da (2007)
Potato (Solanum tuberosum L.) is the most important horticultural crop of the world. Late blight (Phytophthora infestans (Mont.) de Bary) is the most important and devastating disease. There is no cultivar with sufficient level of resistance in Brazil being most part of production costs used for its control. Besides late blight resistance, new cultivars should have high tuber quality either for processing or table stock. The objectives of this study were to a) develop progeny of late blight resistant progenitors; b) compare selection for tuber quality in single and eight hill plots; c) identify clones with high tuber quality for processing or table stock; and d) study culture medium to increase growth and sporulation of P. infestans isolates. rosses among late blight resistant clones (SMIJ319-1, SMIJ456-4Y, SMIG274-3, Torridon, Tollocan e Stirling) and clones or cultivars either with high tuber quality or highly adapted were made in a screen house of Fitotecnia Department of Universidade Federal de Santa Maria during 2005. Twenty families were evaluated in single hill during spring 2006. Selected clones were also evaluated in eight hill plots during autumn 2006. Tuber appearance, specific gravity and chip color were assessed in all selected clones of both clonal generations. The 19 selected new clones were then evaluated in twenty hill plots during spring 2006 for tuber appearance, chip color, contents of dry matter, reduced sugars, starch and amylose. Growth and sporulation of P. infestans isolates were assessed in potato-dextrose-agar (PDA), carrot-agar, corn flour-agar, rye B and juice of eight vegetables (V8) culture mediums. A high percentage of clones combined tuber appearance, specific gravity and chip color and were identify in progeny of Tollocan, Stirling, SMIJ319-1 e SMIJ456-4Y. A moderate selection index resulted in 89.4%, 63.9% and 79.8% selections in single hill and 71.2%, 63.9% and 71.4% selections in eight hill plots respectively for tuber appearance, specific gravity and chip color. The clones SMA501-1, SMA508-2, SMA508-4, SMA514-8, SMA514-10, SMA514-11 e SMA520-5 showed high processing potential. The clones SMA504-2, SMA505-2, SMA505-7, SMA506-4, SMA513-2, SMA516-2, SMA517-2, SMA519-1 e SMA520-5 showed high potential either for processing or table stock. The rye B medium increased mycelium growth of P. infestans and the culture mediums PDA and V8 increased sporangium production